Enforcement of the Death Penalty for Corruptors Who Perform Corruption Crimes During a Pandemic (Case Study: The Enrapture of Two Ministers Related to Corruption Cases During the Covid19 Pandemic) - Ciprian Caesar; Edward Wira Hamonangan Naibaho (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The existence of corruption cases during the pandemic carried out by ministerial-class officials, namely the former Minister of Maritime Affairs and Fisheries, Edhy Prabowo, and former Minister of Social Affairs, Juliari Batubara, is enough to make the public angry. Considering his actions were carried out when the country was experiencing a crisis and the community had to work hard in dealing with the pressures of the COVID19 pandemic. This indicates that acts of corruption have entered an emergency or critical period so that heavier penalties must be applied immediately. This is necessary to answer the wishes of the community to provide legal firmness for the corruptors so that similar incidents do not happen again. Based on the above case, the relevance of the application of the death penalty to corrupt officials will be analyzed. This study uses a qualitative descriptive research method so that a solution is found to determine the death penalty according to and in line with the process of nation-building. The result is, the Corruption Eradication Law in the provision of legal quantity needs to be evaluated in this case applying the death penalty for criminals for public money. This will show the determination of the government in this case legal institutions in providing legal certainty to the community to minimize acts of corruption in the future.